Multi-physics analysis of squeezing fluid flow with rotational, magnetic field, and heat transfer interactions - Zada, Jan; Farooq, Muhammad; Khan, Aamir; Salleh, Zabidin; Rezapour, Shahram; İnç, Mustafa (Elsevier, 2024)
This research paper presents a comprehensive study on the intricate interplay of rotational, magnetic field and heat transfer effects in squeezing fluid flow, utilizing the foundational framework of Navier-Stokes equations. Fluid flow in confined geometries has significant applications in various industrial processes, including lubrication systems, microfluidics, and heat exchangers. The integration of rotational motion, magnetic fields, and heat transfer phenomena into this context holds immense potential for optimizing performance and efficiency. The study commences with the derivation and analysis of the coupled Navier-Stokes equations, incorporating the Coriolis force due to rotational motion, the Lorentz force arising from magnetic fields, and the energy equation for heat transfer. This comprehensive model accounts for the complex interactions between these physical phenomena, offering a holistic perspective on squeezing fluid flow dynamics. Numerical analysis are conducted to investigate the behavior of fluids under the influence of rotational, magnetic field, and heat transfer effects. The results reveal intricate flow patterns, including vortex formation and heat transfer enhancement. Furthermore, the impact of key parameters such as rotational speed, magnetic field strength, and temperature gradients on flow characteristics is systematically analyzed. The Dufour effect pertains to the transfer of energy resulting from a gradient in mass concentration, occurring as a correlated consequence of irreversible processes. It functions as the inverse of the Soret effect. The temperature changes due to the concentration gradient, amplifying as the Dufour number increases. The most significant temperature rise is observed at the midpoint of the fluid domain. Conversely, the Soret number behaves in a similar but opposite manner. Tables 4-10 has been created to offer a comprehensive analysis of the optimal alignment between Homotopy Analysis Method (HAM) and BVP4c. Specifically, it demonstrates a continuous decrease in skin friction for xi(S0), xi(Rd), xi(R2), and while showing an increase for xi(S0), xi(D0), and xi(Rem). Meanwhile, the skin friction remains constant for xi(Pr). The research centers on analyzing heat and mass transfer properties within an incompressible fluid confined between two rotating and stretching disks amidst an unpredictable flow pattern. The study employs a blend of analytical and numerical approaches to solve the governing equations, delving into the intricate fluid dynamics and the intricate processes of heat and mass transfer within this intricate system.
Keywords: Squeezing fluid flow; Coupled Navier-Stokes equations; Heat transfer interactions; Numerical solution